THE APPLICATION OF ELECTRONIC GOVERNMENT TO THE QUALITY OF PUBLIC SERVICES: A Case Study of the Population and Civil Registry Office Ambon - Kriekhoff, Shella (Srawung: Journal of Social Sciences and Humanities, 2023)
The application of information and communication technology in the public sector in order to improve the quality service to the public is indispensable. Since the government is required to implement good governance and improve the quality of public services, it has become a driving force in the application of electronic government as a system that uses information technology in government agencies, including the Population and Civil Registry Office Ambon. Therefore, this research aims to determine the effect of the application of electronic government to the quality of public services at the Population and Civil Registry Office Ambon. The method used in the research is simple linear regression analysis. In addition, the retrieval technique used a census technique in which 35 populations were sampled in this research. Those people derived from consumers who have received services from the Population and Civil Registry Office Ambon. Furthermore, the result of this research indicated that there is a significant effect between the application of e-government and improving the quality of public services at the Population and Civil Registry Office Ambon, it is proven by significant results by comparing the amount of the t-count value of 8.363 and the t-table value of 1.684 (t-count 8.363> t-table 1.684). In addition, e-government contributes 67.9% to the quality of public services while the rest 32.1% is affected by other variables.